DRASIN KINGDOM - Bella chu (Manes Wordworks, 2025)
In the Drasin Kingdom, where magic brews beneath royal masks, two unlikely hearts clash as fate pulls them together. Half-human, half-fae Helena has spent years hiding her power to travel between realms. She never sought the crown’s favour, but when her abilities become the kingdom’s last hope, her heart is tested—especially by the man who once shattered it. Prince Alaric, haunted by his father’s prophecy that he will bring down the kingdom, fights to prove everyone wrong. Surrounded by those who wish for his failure, he can no longer deny his desire for Helena. He needs her. With the double threat of magic and betrayal, they must find a cure for their people and summon a dragon to save the kingdom. But will they defy the odds, or will Alaric’s father’s nightmare come true?